Piercing Proverbial Crows’ Eyes: Theft and Publication in Renaissance France - Herdman, Emma (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2020)
The ironic Latin proverb “cornicum oculos configere” was classically illustrated by the example of Gnaeus Flavius, celebrated for his theft and valuable but unauthorized publication of Rome’s legal secrets. Erasmus’s discussion of the proverb in the Adages consequently focuses on the tension within the transfer of knowledge between openness and secrecy, and on the fragile status of intellectual authority within a scholarly domain made increasingly public by the printing press. This article uses the example of Flavius to trace the idea of theft within Renaissance attitudes to the possession and dissemination of knowledge. It compares the reception of Flavius in three contexts: Erasmus’s ambivalence towards publication as a form of theft in the Adages; ancient criticisms of theft as social presumption; and the more positive representation of epistemological theft in the works of four Renaissance French jurists. It thus argues that Erasmus represents a turning point both in the reception history of Flavius and in attitudes to intellectual theft—and thereby to intellectual property—in the Renaissance.